Neurochemical Systems of the Retina Involved in the Control of Movement - Willis, Gregory L.; Freelance, Christopher B. (Frontiers in Neurology, 2017)
Recent studies have revealed that the retina may exert control over deep brain function and may be importantly involved in the aetiology, progression and treatment of disorders such as Parkinson’s disease (PD). While such a concept is uncharted territory and even less is known about the mechanism by which this might be achieved, the present study was undertaken to determine how retinal dopamine (DA), serotonin (5HT) and melatonin neurotransmitter systems might be involved in the control of movement in its own right. To explore these further, intravitreal (IVIT) injections of DA, 5-HT and melatonin were made 0.5 or 3 hrs prior to testing horizontal and vertical movement in the open field as well as assessment on 3 motor tests used routinely to evaluate movement as a preclinical model of PD. The doses of DA (2 μl of 25 and 75 μg/μl), 5HT (2 μl of 5 and 15 μg/μl) and melatonin (2 μl of 5 μg/μl) were chosen because of previous work demonstrating an anatomically precise effect of these transmitters after they were injected directly into the brain. The post-injection times of testing were also chosen on the basis of previous intracerebral and IVIT work intimating the importance of the circadian cycle in determining the efficacy of such effects. While significant effects were seen in all drug treated groups compared to controls, these effects were either increased or decreased in accordance with the phase of the light/dark cycle. Changes in movement were also relative to the compound injected, the dose of injectate and the time of observation after injection. The present results illustrate that specific retinal neurotransmitter systems are involved in the normal control of bodily motor function. This work compliments recent studies suggesting that the retina is an anatomical locus involved in the aetiology, progression of PD and providing a new entity for more effective treatment.